One Health: governance and regulatory framework for antimicrobial use in Malawi - Mhone, Amos L.; Muloi, Dishon M.; Moodley, Arshnee (Elsevier, 2025)
Background: Antimicrobial resistance (AMR) poses a global threat to both human and animal health, associated with widespread use of antimicrobials across sectors. In low- and middle-income countries (LMICs) such as Malawi, weak regulatory frameworks and limited enforcement capacity contribute to inappropriate use of antibiotics.